Analisis Rasio Kontribusi Pajak Daerah Terhadap Pendapatan Asli Daerah di Kabupaten Pasaman Untuk Mengoptimalkan Manajemen Pendapatan Daerah - Halkadri Fitra (Wahana Riset Akuntansi, 2015)
The purpose of this study was to determine the actual contribution of local taxes to the realization of local revenues in Pasaman regency period 2010 to 2014. This type of research is classified as descriptive research with data collection techniques used are secondary data documentation method realization reports and reports on the realization of local tax revenue area. The results showed that local tax revenues from 2010 to 2014 always increase with an average increase of 20.10% per year. Contributions realization of local taxes to the realization of local revenue for 2010 was 18.40%, in 2011 amounted to 14.16%, in 2012 amounted to 13.38%, in 2013 amounted to 11.28% and in 2014 amounted to 8.45% with average contribution in the realization of local taxes to the realization of local revenue is 13.13%. Elements of local taxes that provide the largest contribution to the increase in local revenues is street lighting tax with an average contribution during the five-year study period was 7.386%. Based on the research results it is suggested to Pasaman district government to increase tax realization in order to make a breakthrough and innovation, and improving the quality of services to taxpayers and continue to explore the potential of existing taxes and in accordance with applicable rules.Keywords: tax contribution ratio, local revenue, local revenue management